1997
DOI: 10.1111/j.1432-1033.1997.0283a.x
|View full text |Cite
|
Sign up to set email alerts
|

The Interactions with Solvent, Heat Stability, and 13C‐Labelling of Alamethicin, an Ion‐Channel‐Forming Peptide

Abstract: The peptide alamethicin was labelled with I3C and "N by growing the fungus Trichoderma viride in a medium containing [U-"C]glucose and K"N0,. Spin-echo difference spectroscopy showed that I3C was incorporated to a level of about SO% and "N to about 98%. Incorporation of "C into the peptide provided residue-specific probes of the interactions with solvent and heat stability of this ion-channelforming peptide. All of the carbonyl carbons and the a-carbons of the a-aminoisobutyric acid [Ala(Me)J residues of alame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 57 publications
3
13
0
Order By: Relevance
“…Moreover, the C¼O group of Gly 6 , and the amide H-atoms of Aib 8 and Aib 9 are exposed to solvent and form the site of a strong hydration in the middle of the molecule. The 1 J NC pattern for Aam-I is more similar to that observed in alamethicin [45] than to that in Zrv-IIB, where no significant backbone hydration was observed [39].…”
supporting
confidence: 66%
“…Moreover, the C¼O group of Gly 6 , and the amide H-atoms of Aib 8 and Aib 9 are exposed to solvent and form the site of a strong hydration in the middle of the molecule. The 1 J NC pattern for Aam-I is more similar to that observed in alamethicin [45] than to that in Zrv-IIB, where no significant backbone hydration was observed [39].…”
supporting
confidence: 66%
“…Chemical shift, ROE, and circular dichroism measurements on alamethicin suggest that the molecule is less flexible at lower temperatures (Esposito et al, 1987;Yee et al, 1996). However, the measured order parameters do not seem to be sensitive to this difference (Fig.…”
Section: Model-free Analysismentioning
confidence: 98%
“…The dynamics of seven of the non-Aib c~-carbons in alamethicin and some of the side chains were investigated by natural abundance ~3C NMR spectroscopy by Kelsh et al (1992). Alamethicin is well-suited to relaxation-rate analysis, as it can be labelled with 15N (Yee and O'Neil, 1992) and 13C (Yee et al, 1996). To investigate the dynamics of alamethicin at both the L-amino acids and the Aib residues, we have measured residue-specific ~SN relaxation data for uniformly labelled alamethicin dissolved in methanol and in aqueous sodium dodecylsulfate (SDS) solution.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the b-helical structures of gramicidin A fail to melt in octanol at temperatures up to 65 8C; [39] likewise, Seebach reported that the 3 14 -helical structures of a b 3 hexapeptide and a b 3 heptapeptide remained largely intact up to 60 8C in methanol, [42] and others have shown that 3 10 -helical peptides rich in the a,a-dialkylated residue a-aminoisobutyric acid (Aib) exhibit exceptional thermal stability. [40,41] The high thermal stability observed in these systems has been attributed to a dominance of steric effects over hydrogen bonding, and Wu et al have advanced a related explanation for the high thermal stability of b 3 -peptide 3 14 helices in particular. On the basis of theoretical calculations, these authors reported that, in contrast to a-helical peptides, the helical and extended forms of model b 3 peptides are similar in entropy, and, thus, no large entropic driving force exists for unfolding at elevated temperatures.…”
Section: Intramolecular Hydrogen Bonding In 1 Mmentioning
confidence: 99%